2022
DOI: 10.1186/s12879-022-07765-w
|View full text |Cite
|
Sign up to set email alerts
|

Safety of a Novel ESAT6-CFP10 skin test compared with tuberculin skin test in a double-blind, randomized, controlled study

Abstract: Background ESAT6-CFP10 (EC) skin test has been reported accurate and safe in identifying tuberculosis infection. We aimed to demonstrate the safety of EC skin test compared with tuberculin skin test (TST) in university freshmen. Methods We conducted a double-blind, randomized, controlled clinical study in a university freshmen population with 16,680 participates in China, and finally 14,579 completed the study. About a half received an EC skin test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Among those, 7 studies reported on Cy-Tb [ 8–13 ], 5 on C-TST [ 14–16 ], and 11 on Diaskintest [ 17–27 ]. The updated search identified 2 additional C-TST studies [ 28 , 29 ]. We also found studies of early products that were not translated into the final products ( Supplementary Table 1 ) [ 30–35 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among those, 7 studies reported on Cy-Tb [ 8–13 ], 5 on C-TST [ 14–16 ], and 11 on Diaskintest [ 17–27 ]. The updated search identified 2 additional C-TST studies [ 28 , 29 ]. We also found studies of early products that were not translated into the final products ( Supplementary Table 1 ) [ 30–35 ].…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, 2 tests were administered ≥30 minutes apart. The updated search also found a study that randomly administered C-TST in 1 group and TST in the other group while blinding the allocation [ 29 ]. Two studies did not compare C-TST and TST.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations